Deep ultraviolet photoluminescence studies of Al-rich AlGaN and AlN epilayers and nanostructures - Nepal, Neeraj (Kansas State University, 2006)
Deep ultraviolet (UV) photoluminescence (PL) spectroscopy has been employed to study optical properties of AlGaN alloys, undoped and doped AlN epilayers and nanostructure AlN photonics crystals (PCs). Using a deep UV laser system with an excitation wave length at 197 nm, continuous wave PL, temperature dependent, and time-resolved PL have been carried out on these AlGaN and AlN epilayers and nanostructures. We have measured the compositional and temperature dependence of the energy bandgap of AlxGa1-xN alloys covering the entire alloy range of x, 0 â ¤ x â ¤ 1 and fitted with the Varshni equation. Varshni coefficients, alpha and betaï ¬ in AlGaN alloys have a parabolic dependence with alloy concentration x. Based on the experimental data, an empirical relation was thus obtained for the energy gap of AlGaN alloys for the entire alloy concentration and at any temperature below 800 K. The exciton localization energy in AlxGa1-xN alloys the entire composition range (0 â ¤ x â ¤ 1) has been measured by fitting the band edge emission peak energy with the Varshni equation. Deviations of the excitonic emission peak energy from the Varshni equation at low temperatures provide directly the exciton localization energies, ELoc in AlGaN alloys. It was found that ELoc increases with x for x â ¤ 0.7, and decreases with x for x â ¥ 0.8. The relations between the exciton localization energy, the activation energy, and the emission linewidth have been established. It thus provides three different and independent methods to determine the exciton localization energies in AlGaN alloys. Impurity transitions in AlGaN alloys have also been investigated. Continuous wave (CW) PL spectra of Si and undoped AlGaN alloys reveals groups of impurity transitions that have been assigned to the recombination between shallow donors and an isolated triply charged cation-vacancy (VIII)3-, a doubly charged cation-vacancy-complex (VIII-complex)2-, and a singly charged cation-vacancy-complex (VIII-complex)-1. The energy levels of these deep acceptors in AlxGa1-xN (0 â ¤ x â ¤ 1) alloys are pinned to a common energy level in the vacuum. AlGaN alloys predominantly exhibiting the bandedge and (VIII-complex)1- transitions possess improved conductivities over those emitting predominantly (VIII)3- and (VIII-complex)2- related transitions. These results thus answer the very basic question of high resistivity in Al-rich AlGaN alloys. Acceptor doped AlGaN alloys have been studied by deep UV PL. A PL emission line at 6.02 eV has been observed at 10 K in Mg-doped AlN. It is due to the recombination of an exciton bound to the neutral Mg acceptor (I1) with a binding energy, Ebx of 40 meV, which indicates large activation energy of the Mg acceptor. The observed large binding energy of the acceptor-bound exciton is consistent with relatively large binding energy of the Mg acceptor in AlN. With the energy level of 0.51 eV for Mg dopants in AlN, it is interesting and important to study other suitable acceptor dopants for AlN. Growth and optical studies of Zn-doped AlN epilayers has been carried out. The PL spectra of Zn-doped AlN epilayers exhibited two impurity emission lines at 5.40 and 4.50 eV, which were absent in undoped epilayers. They are assigned respectively, to the transitions of free electrons and electrons bound to triply positively charged nitrogen vacancies (0.90 eV deep) to the Zn0 acceptors. It was deduced that the Zn energy level is about 0.74 eV above the valence band edge, which is about 0.23 eV deeper than the Mg energy level in AlN. Nitrogen vacancies are the compensating defects in acceptor doped AlGaN alloys. A nitrogen vacancy (VN) related emission line was also observed in ion-implanted AlN at 5.87 eV and the energy level of singly charged VN1+ is found at 260 meV below the conduction band. As a consequence of large binding energy of VN1+ as well as high formation energy, VN1+ in AlN cannot contribute significant n-type conductivity, which is consistent with experimental observation. The temperature dependent PL study of the bandedge emissions in GaN and AlN epilayers up to 800 K has been carried out, which reveals two distinctive activation processes. The first process occurring below Tt = 325 K (Tt = 500 K) for GaN (AlN) is due to the activation of free excitons to free carriers, whereas the second occurring above Tt with an activation energy of 0.29 eV (0.3 eV) for GaN (AlN) is believed to be associated with a higher lying conduction band (ï 3) at about 0.3 eV above the conduction band minimum (ï 1). These higher lying bands could affect device performance of GaN and AlN at elevated temperatures. Two-dimensional nanostructured AlN photonic crystals (PCs) with a varying periodicity/diameter down to 150 nm/75 nm have also been studied by deep UV PL. With PCs formation, a 20-fold enhancement in the band edge emission intensity at 208 nm over unpatterned AlN epilayer has been observed. The emission intensity increases with the decrease in the lattice constant of the AlN PCs. AlN PCs represent photonic crystals with highest (shortest) bandgap (wavelength) semiconductors, which open up new opportunities for exploring novel physical phenomena in the artificially structured photonic band gap material systems and their applications, particularly in the area of deep UV as well as nano-photonics.
Keywords: photoluminescence; localized exciton; AlGaN alloy; deep impurity transition; Photonic crystals; Optical property; Physics, Condensed Matter (0611)